The Impact of Income Inequality, Foreign Investment, and Inflation on Gross Domestic Product in Indonesia - Trimurti, Christimulia Purnama (Yayasan Riset dan Pengembangan Intelektual, 2025)
Economic growth is an important economic instrument for the progress of a country so that the welfare of the people improves. Therefore, the government needs to pay attention to income inequality, investment, and maintaining price stability. Therefore, this study aims to analyze the impact of income inequality, foreign investment, and inflation on economic growth. For this purpose, data from 10 years, from 2014 to 2023, has been considered and analyzed using time series regression. The results of the study show that there is no significant impact of income inequality, foreign investment, and inflation on economic growth. It is recommended that the government focus on promoting inclusive economic growth by targeting the strengthening of the informal sector and underdeveloped regions, expanding the scope of education, training, and productivity programs for low-income communities, and expanding purchasing power and economic inclusion, which are more important in maintaining the balance between prices and growth.